Peningkatan Masa Pakai Pisau Gergaji Tungsten Carbide Berpelapis dalam Pemotongan Medium Density Fiberboard - Kidung Tirtayasa Putra Pangestu; Christina Dekawati Putri Lingga; Wayan Darmawan (Institut Pertanian Bogor, 2023)
The scarcity and high cost of high-quality sawn timber has resulted in the switching of furniture industry to using composite wood such as medium density fiberboard (MDF) as the raw material for its products. One of the factors that affect production costs and product quality in the furniture industry is the quality of the cutting tool used in the cutting operation. The quality of the cutting tool could be improved through the addition of coatings on the surface of cutting tool (surface coating). The purpose of this study was to determine the life time of AlCrN, TiAlN, and TiN coated tungsten carbide (TC) tools in cutting MDF. Cutting operations were performed on a computer numerical control (CNC) router machine at feed per revolution (Frev) of 0,10, 0,15, 0,20, and 0,30 mm/rev. The TC cutting tool life was determined based on its wear and was calculated using the Taylor tool life formula. The results showed that coated TC cutting tool provided a better wear resistance and longer life than uncoated TC cutting tool. The low of Frev set in cutting MDF resulted in a lower wear and longer life of cutting tool. AlCrN coated TC cutting tool provided the best wear resistance and longest life, thus it promising to be developed and used in cutting MDF. Keywords: coated cutting tool, medium density fiberboard, surface coating, tool life, wear